Potensi Tiga Jenis Kayu Tanah Gambut Sumatera sebagai Bahan Baku Pulp dan Kertas (The Potential of Three Peat Land Woods of Sumatera as Pulp and Paper Raw Material) - Kanti D Rizqiani; Yeni Aprianis; Ahmad Junaedi (Masyarakat Peneliti Kayu Indonesia, 2019)
The growth of pulp and paper industries has encouraged the expansion of the industrial plantation forests for pulp wood. The exotic species planted for pulp wood initially maintained a relatively high productivity, however it decreases in the following rotation cycles. The peat land wood species of Sumatera could be an alternative for exotic species. However, the insufficient information on the wood properties has brought about they are less considered. This paper examined the fiber quality of Sumatran local peat-wood and its possibility as a raw material of pulp and paper. For specific gravity, samples were selected based on three different diameter groups in each plot. Fiber properties (dimension and fiber derivative values) used to asses the suitability of the wood for pulp and paper raw material were determined in accordance with the method of the Forest Product Laboratory (FPL). The resulted data and information were compared to those of krasikarpa (Acacia crassicarpa Benth.). The results showed that the fiber quality of sekubung wood was classified into grade II, while gerunggang and mahang putih were classified into grade III. The specific gravity of gerunggang wood was higher than these of other woods and comparable to that of krasikarpa. Although the growth of Sumatran local peat-wood is still low, however, conformity with government regulations (Government Regulation Number 57-2016 and Ministry of Environment and Forestry Regulation Number 17-2017) and fiber quality, the local peat-wood could potentially substitute the exotic wood species.